THE HISTORY OF THE DIPODOIDEA (RODENTIA, MAMMALIA) IN THE MIOCENE OF ASIA: 4. DIPODINAE AT THE MIOCENE-PLIOCENE TRANSITION - Zazhigin V.S.; Lopatin A.V. (My University, 2001)
Late Miocene and Early Pliocene three-toed jerboas from Mongolia, Tuva, Kazakhstan, and the southern part of Western Siberia are investigated. The earliest members of the genera Dipus, Stylodipus, Plioscirtopoda, and Jaculus are indicated. The following twelve species are described: Late Miocene Dipus conditor sp. nov., Plioscirtopoda antiqua sp. nov., and Jaculus sibiricus sp. nov.; Early Pliocene Dipus essedum sp. nov., D. singularis sp. nov., Stylodipus iderensis sp. nov., S. perfectus sp. nov., Plioscirtopoda rapida sp. nov., P. zykini sp. nov., and Jaculodipus yavorensis gen. et sp. nov.; and Miopliocene Scirtodipus kazakhstanicus Savinov, 1970 and Dipus fraudator (Schlosser, 1924). The taxonomic composition of the extinct Dipodinae is revised.
Keywords: Pliocene; Miocene; Dipodoidea; Mongolia; Kazakhstan; Tuva; Western Siberia; Cenozoic::Neogene::Pliocene; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Плиоцен; Кайнозой::Неоген::Миоцен